2004
DOI: 10.1242/jcs.01481
|View full text |Cite
|
Sign up to set email alerts
|

MAP kinases and cell migration

Abstract: Recent studies have demonstrated that mitogen-activated protein kinases (MAPKs), including Jun N-terminus kinase (JNK), p38 and Erk, play crucial roles in cell migration. JNK, for example, regulates cell migration by phosphorylating paxillin, DCX, Jun and microtubule-associated proteins. Studies of p38 show that this MAPK modulates migration by phosphorylating MAPK-activated protein kinase 2/3 (MAPKAP 2/3), which appears to be important for directionality of migration. Erk governs cell movement by phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
842
3
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 986 publications
(891 citation statements)
references
References 132 publications
38
842
3
8
Order By: Relevance
“…Mammalian cells contain three major classes of MAPK: ERK, JNK, and p38. All three kinases have been shown to play crucial roles in cell migration by distinct mechanisms [35]. Our results confirm the importance of EKR, JNK and p38 MAPK also for b-defensin-induced chemotaxis of macrophages and mast cells.…”
Section: Discussionsupporting
confidence: 84%
“…Mammalian cells contain three major classes of MAPK: ERK, JNK, and p38. All three kinases have been shown to play crucial roles in cell migration by distinct mechanisms [35]. Our results confirm the importance of EKR, JNK and p38 MAPK also for b-defensin-induced chemotaxis of macrophages and mast cells.…”
Section: Discussionsupporting
confidence: 84%
“…This indicates that isoginkgetin could inhibit other pathways that regulate cell invasion. Although mitogen-activated protein kinases, such as ERK and p38, do not regulate MMP-9 expression in HT1080 cells, they have shown to be important for cell invasion and migration (29,30). Therefore, we examined the effect of isoginkgtin on mitogen-activated protein kinases and found that Results were statistically significant (*, P < 0.01) using Student's t test.…”
Section: Discussionmentioning
confidence: 95%
“…MEK-ERK may regulate cell motility by preventing formation of extensive actin stress fibers via suppression of tropomyosin induction by TGF-b1 (Bakin et al, 2004) or inhibition of RhoA-Rho kinase pathway (Sahai et al, 2001;Pawlak and Helfman, 2002). JNK may regulate motility by modulating the dynamics of microtubules (Huang et al, 2004) or by affecting the assembly/ stability of focal adhesion complexes via phosphorylation of paxillin and Spir, a WASP family protein (reviewed by Huang et al (2004)). The role of JNK in TGF-b-mediated cell motility, however, is less defined, given that inhibition of JNK does not affect TGF-bmediated actin remodeling and epithelial to mesenchymal transition (EMT) (Bhowmick et al, 2001a;Bakin et al, 2002Bakin et al, , 2004Edlund et al, 2002).…”
Section: Discussionmentioning
confidence: 99%